Different effects of sodium chloride preincubation on cadmium tolerance of Pichia kudriavzevii and Saccharomyces cerevisiae. (26th February 2015) - Ma, Ning; Li, Chunsheng; Dong, Xiaoyan; Wang, Dongfeng; Xu, Ying
<x xml:space="preserve">Abstract</x> Application of growing microorganisms for cadmium removal is restricted by high cadmium toxicity. The effects of sodium chloride (NaCl) preincubation on the cadmium tolerance and removal ability of Pichia kudriavzevii and Saccharomyces cerevisiae were investigated in this study. NaCl preincubation improved the biomass of P. kudriavzevii under cadmium stress, while no obvious effect was observed in S. cerevisiae. The improved activities of peroxidase (POD) and catalase (CAT) after NaCl preincubation might be an important reason for the decrease of the reactive oxygen species (ROS) accumulation, cell death, and oxidative damage of proteins and lipids induced by cadmium, contributing to the improvement of the yeast growth. The cadmium bioaccumulation capacity of P. kudriavzevii decreased significantly after NaCl preincubation, which played an important role in mitigating the cadmium toxicity to the yeast. The cadmium removal rate of P. kudriavzevii was obviously higher than S. cerevisiae and was significantly enhanced after NaCl preincubation. The results suggested that NaCl preincubation improved the cadmium tolerance and removal ability of P. kudriavzevii.